Mechanistic insights into resistance mechanisms to T cell engagers - Cao, Linlin; Leclercq-Cohen, Gabrielle; Klein, Christian; Sorrentino, Antonio; Bacac, Marina (Frontiers in Immunology, 2025)
T cell engagers (TCEs) represent a groundbreaking advancement in the treatment of B and plasma cell malignancies and are emerging as a promising therapeutic approach for the treatment of solid tumors. These molecules harness T cells to bind to and eliminate cancer cells, effectively bypassing the need for antigen-specific T cell recognition. Despite their established clinical efficacy, a subset of patients is either refractory to TCE treatment (e.g. primary resistance) or develops resistance during the course of TCE therapy (e.g. acquired or treatment-induced resistance). In this review we comprehensively describe the resistance mechanisms to TCEs, occurring in both preclinical models and clinical trials with a particular emphasis on cellular and molecular pathways underlying the resistance process. We classify these mechanisms into tumor intrinsic and tumor extrinsic ones. Tumor intrinsic mechanisms encompass changes within tumor cells that impact the T cell-mediated cytotoxicity, including tumor antigen loss, the expression of immune checkpoint inhibitory ligands and intracellular pathways that render tumor cells resistant to killing. Tumor extrinsic mechanisms involve factors external to tumor cells, including the presence of an immunosuppressive tumor microenvironment (TME) and reduced T cell functionality. We further propose actionable strategies to overcome resistance offering potential avenues for enhancing TCE efficacy in the clinic.